صلاحية أملاح مملحة سنيسلة للاستهلاك البشري _ دراسة في الجغرافية الطبيعية (Journal of the College of Basic Education, 2026)
The Sinisla salt marsh is located in the Al-Jazeera region, northwest of Iraq, with an area estimated at (76) km2. It is a low-lying area compared to the surrounding areas, and is flooded with water in the winter and dries up in the summer, which leads to the deposition of salts on the surface of the marsh. This study deals with a study of physical geography, as salt marshes are one of the geomorphological phenomena with dissolving units, evaporative units, and sedimentary units of erosion origin, represented by On the edges surrounding the salt marsh, which are exposed to erosion1-The researcher took (5) samples of saline solutions from the surface of the marsh. The samples were taken during the period of high salt concentration (April), when a large portion of the water evaporates, leaving the super-saline water on the surface of the marsh. Laboratory analysis results showed that the salt marsh is rich in sodium chloride salts, but it is not suitable for direct human use until it undergoes a series of salt refining processes and removing impurities from it2-Part of the research was devoted to studying the hydrogeomorphology of the Sanisla salt marsh and the lands adjacent to it in the Al-Jazeera region, and studying the sources of water feeding the marsh. Most of these sources were seasonal flows, flooded with water in the winter and dried up in the summer. In addition, the groundwater level rose during the winter and the water rose by capillary action. The geomorphological units were studied and drawing a hydrogeomorphological map and clarifying the geomorphological units in the study area on the map, which are units of erosion origin, dissolution form units, river form units, evaporation form units, and man-made form units .